Transitional Changes in Fatigue-Related Symptoms Due to Long COVID: A Single-Center Retrospective Observational Study in Japan - Nakano, Yasuhiro; Otsuka, Yuki; Honda, Hiroyuki; Sunada, Naruhiko; Tokumasu, Kazuki; Sakurada, Yasue; Matsuda, Yui; Hasegawa, Toru; Ochi, Kanako; Hagiya, Hideharu; Kataoka, Hitomi; Ueda, Keigo; et al. (Medicina (Kaunas, Lithuania), 2022)
Background and Objectives: Changes in post COVID-19 condition (PCC) characteristics caused by viral variants have yet to be clarified. We aimed to characterize the differences between clinical backgrounds and manifestations in long COVID patients who were infected with the Delta variant and those who were infected with the Omicron variants. Materials and Methods: This study was a single-center retrospective observational study for patients who visited our COVID-19 aftercare outpatient clinic (CAC) established in Okayama University Hospital (Japan) during the period from 15 February 2021 to 15 July 2022. We classified the onset of COVID-19 in the patients into three groups, the preceding, Delta-dominant, and Omicron-dominant periods, based on the prevalent periods of the variants in our prefecture. Results: In a total of 353 patients, after excluding 8 patients, 110, 130, and 113 patients were classified into the preceding, Delta-dominant, and Omicron-dominant periods, respectively. Patients infected in the Omicron-dominant period had significantly fewer hospitalizations, milder illnesses, more vaccinations and earlier visit to the CAC than did patients infected in the Delta-dominant period. Patients infected in the Omicron-dominant period had significantly lower frequencies of dysosmia (12% vs. 45%, ** p < 0.01), dysgeusia (14% vs. 40%, ** p < 0.01) and hair loss (7% vs. 28%, ** p < 0.01) but had higher frequencies of fatigue (65% vs. 50%, * p < 0.05), insomnia (26% vs. 13%, * p < 0.05) and cough (20% vs. 7%, ** p < 0.01) than did patients infected in the Delta-dominant period. Conclusions: The transitional changes in long COVID symptoms caused by the two variants were characterized.